2003
DOI: 10.1186/1471-2156-4-s1-s90
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two analytic strategies to detect linkage to obesity with genetically determined age of onset: the Framingham Heart Study

Abstract: Background: Genes have been found to influence the age of onset of several diseases and traits. The occurrence of many chronic diseases, obesity included, appears to be strongly age-dependent. However, an analysis of potential age of onset genes for obesity has yet to be reported. There are at least two analytic methods for determining an age of onset gene. The first is to consider a person affected if they possess the trait before a certain age (an early age of onset phenotype). The second is to define the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Three additional analyses were supportive in this region: one for another BMI phenotype (overweight, BMI 427 kg/m 2 ), but the remaining two for a low TG:HDL ratio. The signal for the overweight phenotype [Engelman et al, 2003], however, was at 134.1 cM, and was much closer to that of Moslehi et al [2003], compared with those for a low TG:HDL ratio [Horne et al, 2003], which were more telomeric (161.7 cM) and may indicate a different region. If this is the case, this region may be more likely involved in body mass, rather than the complete syndrome.…”
Section: Discussion Summary Of Linkage Regions Identified In the Gaw1supporting
confidence: 62%
See 3 more Smart Citations
“…Three additional analyses were supportive in this region: one for another BMI phenotype (overweight, BMI 427 kg/m 2 ), but the remaining two for a low TG:HDL ratio. The signal for the overweight phenotype [Engelman et al, 2003], however, was at 134.1 cM, and was much closer to that of Moslehi et al [2003], compared with those for a low TG:HDL ratio [Horne et al, 2003], which were more telomeric (161.7 cM) and may indicate a different region. If this is the case, this region may be more likely involved in body mass, rather than the complete syndrome.…”
Section: Discussion Summary Of Linkage Regions Identified In the Gaw1supporting
confidence: 62%
“…Another group used modeling to construct the phenotype as part of a broader new methodological approach [Ghosh et al, 2003]. One group focused on age at onset, using in part a survival approach [Engelman et al, 2003]. It should be noted that one other critical approach, that of repeated measures, was not included in Group 10, but is covered elsewhere [Gauderman et al, 2003].…”
Section: Methods Construction Of Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 19 genome‐wide studies reported during the past year, 11 were based primarily on BMI measurements. Three studies were performed with BMI measures obtained in 1702 individuals from 330 pedigrees of the Framingham Heart Study (267,268,269). In the first study (269), evidence of linkage with BMI between the ages of 40 and 50 years was found on Chromosomes 2p22 (D2S1788), 2p22‐p21 (D2S1356), 2p16.3 (D2S1352), 3q23 (D3S1744), 3q26 (D3S3053), 11q24.1 (D11S4464), 11q24.3 (D11S912) and 11q25 (D11S2359).…”
Section: Linkage Studiesmentioning
confidence: 99%